Gas permeation in amine functionalized silicon rubber membranes - Achalpurkar, Manoj P.; Kharul, Ulhas K.; Lohokare, Harshada R.; Karadkar, Prasad B. (Separation and Purification Technology, 2007)
Silicon rubber (SR) based thin film composite (TFC) membranes find increasing applicability in various industrial separations owing to its excellent thermal and chemical stability. The functionalization of SR would provide enhanced separation characteristics for certain separation applications. The present research focuses on gas permeation properties of dense and thin film composite membranes based on amine substituted silicon rubber (ASR) and unsubstituted silicon rubber (SR). The dense membrane sorption analysis indicated that presence of amine functionality in ASR increased pressure dependant CO2 sorption capacity. Owing to this, an elevation Of CO2 permeability by 15% and CO2 based selectivities by 22-34% in comparison to that of unsubstituted SR was observed. The TFC membranes with SR and ASR as the selective layer on the top of different ultrafiltration (UF) supports with varying properties based on polyacrylonitrile and polysulfone were prepared. The effects of crucial parameters that affected TFC membrane performance, viz., coating solution concentration, UF support membrane porosity and nature of materials were investigated. The preparation of ASR based TFC membranes was demonstrated with a simple crosslinking agent-glutaraldehyde while analyzing effects of crosslinking time on their permeation properties. Polyacrylonitrile (PAN) was found to be better support layer material for ASR based TFC formation than polysulfone (PSF). Thin defect free coating layer can be obtained by appropriate combination of coating solution concentration and support UF membrane porosity. The analysis of effective skin layer thickness of TFC membranes indicated that careful optimization of these parameters is necessary to achieve defect free TFC membranes possessing a good combination of permeance and selectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; Gas permeation; silicon rubber; thin film composite membrane